Metaphors in Practice: Theories-in-Use Among Diverse Community Development Practitioners - Lilian H. Hill; Bernie Moore (Adult Education Research Conference, 1999)
Findings from this grounded theory research indicate that community development practitioners in both North America and Australia create similar working theories based on their experience in communities.